The Role of Social Interaction in Reducing Foreign Language Anxiety: Insights from Indonesian Learners - Rafista, Deviyanti; Ajrina, Kiasati; Rianti, Shafa (English Language Education Study Program, 2025)
Foreign Language Anxiety (FLA) remains a significant barrier to effective language learning, often manifesting as fear, self-doubt, and avoidance of communication. While many studies have explored the causes and effects of FLA, few have investigated its potential solutions, particularly through the lens of social interaction. This study explores how language learners perceive the role of social interaction in reducing anxiety, and what forms of interaction are considered most supportive. Employing a qualitative phenomenological approach, semi-structured interviews were conducted with seven Indonesian learners aged 19–21 who had experienced FLA. Thematic analysis revealed three major findings: (1) learners overwhelmingly preferred paired practice over group activities due to reduced pressure and more personalized feedback; (2) interaction with lecturers often heightened anxiety because of hierarchical power dynamics and fear of evaluation; and (3) some learners never experienced moments of growing confidence, indicating fixed mindsets and a lack of positive reinforcement. The study highlights the importance of emotionally safe learning environments, anxiety-sensitive feedback, and structured peer interaction. These findings suggest that rethinking classroom dynamics—particularly by incorporating dyadic tasks and reducing evaluative stressors—may better support learners in managing FLA.